PEMBELAJARAN INTEGRASI MELALUI MATERI TEMBANG DOLANAN DALAM MATA PELAJARAN BAHASA JAWA DI MI PLUS AL-KAUTSAR YOGYAKARTA - Nurul Ana Sulaikha (Sekolah Tinggi Pendidikan Islam (STPI) Bina Insan Mulia Yogyakarta, 2019)
This study aims to find out that religious values can be integrated throughJavanese language learning in dolanan song material. This type of research isqualitative research with a field research approach (field research). The resultsshowed that integration learning through dolanan song material in Javaneselanguage subjects can instill religious values in students. In Javanese languagelearning must master all four language skills, namely: listening, reading, speaking,and writing. The results of the study show that from the four language skills can beintegrated with religious values.